HIV Testing in the Nation's Opioid Treatment Programs, 2005–2011: The Role of State Regulations. (16th July 2013) - D'Aunno, Thomas; Pollack, Harold A.; Jiang, Lan; Metsch, Lisa R.; Friedmann, Peter D.
<x xml:space="preserve">Abstract</x> Objective To identify the extent to which clients in a national sample of opioid treatment programs (OTPs) received HIV testing in 2005 and 2011; to examine relationships between state laws for informed consent and pretest counseling and rates of HIV testing among OTP clients. Data Source Data were collected from a nationally representative sample of OTPs in 2005 (n = 171) and 2011 (n = 200). Study Design Random‐effects logit and interval regression analyses were used to examine changes in HIV testing rates and the relationship of state laws to HIV testing among OTPs. Data Collection Data on OTP provision of HIV testing were collected in phone surveys from OTP managers; data also were collected on state laws for HIV testing. Principal Findings The percentage of OTPs offering HIV testing decreased significantly from 93 percent in 2005 to 64 percent in 2011. Similarly, the percentage of clients tested decreased from an average of 41 percent in 2005 to 17 percent in 2011. OTPs located in states whose laws do not require pretest counseling and that use opt‐out consent were more likely to provide HIV testing and to test higher percentages of clients. Conclusions The results show the need to increase HIV testing among OTP clients; the results also underscore the beneficial possibilities of dropping pretest counseling as a requirement for HIV testing and of using the opt‐out approach to informed consent for testing.